THE INFLUENCE OF E-DI STRUST, E-NEGATI VE BELIEFS, E-SELF INEFFICACY, E-LOGISTIC EASE, E-CONVENIENCE, E-ENJOYMENT AND SATISFACTION TOWARD LOYALTY BERRYBENKA CUSTOMERS - IRMA SATYA INDRIYANTI; HANNY APRILIA (Media Bisnis, 2021)
The aim of this research is to discover the influence of E-distrust, E-negative beliefs, E-self inefficacy, E-logistic ease, E-convenience, E-enjoyment on Satisfaction, and to discover the influence of Satisfaction on Loyalty. The design of this research is made with descriptive research and causal research. This research is aquantitative study by taking population from consumers who have accounts and shopping experience at Berrybenka website. The samples are taken from the population using purposive sampling method through questionnaires. Total of samples used in this study are 208 respondents. This study uses structural equation model (SEM) with the help of SmartPLS 3.0 analysis program. The results of this research are E-distrust, Enegative beliefs, E-self inefficacy, E-logistic ease, E-enjoyment has impact towards Satisfaction, E-convenience has no impact to Satisfaction, and Satisfaction has impact towards Loyalty.